2014
DOI: 10.1016/j.jpowsour.2014.06.042
|View full text |Cite
|
Sign up to set email alerts
|

Pt–Sn/C catalysts prepared by sodium borohydride reduction for alcohol oxidation in fuel cells: Effect of the precursor addition order

Abstract: A series of Pt-Sn/C catalysts used as anodes during ethanol oxidation are synthesized by a deposition process using NaBH 4 as the reducing agent. The order in which the precursors are added affects the electrocatalytic activity and physical-chemical characteristics of the bimetallic catalysts, where the Pt-Sn catalyst prepared by co-precipitation of both metals functions best below a potential of 0.5 V and the catalyst prepared by sequential deposition of Sn and Pt (drying after Sn addition) is most active abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…The method for preparing the electrocatalyst also plays a vital role in determining the size and reactivity of the nanoparticles, hence the electroactivity. The Pt‐Sn nanoparticles have been synthesized by the Bönneman method , electrodeposition , borohydride reduction method , deposition method , formic acid method and the alcohol reduction method . The alcohol reduction method is the most commonly adopted procedure because of its simplicity.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The method for preparing the electrocatalyst also plays a vital role in determining the size and reactivity of the nanoparticles, hence the electroactivity. The Pt‐Sn nanoparticles have been synthesized by the Bönneman method , electrodeposition , borohydride reduction method , deposition method , formic acid method and the alcohol reduction method . The alcohol reduction method is the most commonly adopted procedure because of its simplicity.…”
Section: Introductionmentioning
confidence: 98%
“…The improved activity of the Pt‐Sn/C electrocatalysts for ethanol oxidation is brought by Sn atoms which serve two functions; (i) Sn provides surface oxygen‐containing species which react with the CO‐like intermediates produced during the oxidation of ethanol and also (ii) modifies the platinum geometric structure resulting in improved activity. It has been observed that Pt‐Sn electrocatalysts give low onset potentials and high current densities during ethanol oxidation in acidic conditions .…”
Section: Introductionmentioning
confidence: 99%
“…Pt catalysts have extensively applied in electro‐oxidation of alcohols with high current density and low onset potential ,. Pt surface modified by foreign metals, such as Bi,, Sn,, Ag,, Pb,, and Sb, etc., can greatly improve the activity or vary the products selectivity. In particular, Bi‐modified Pt catalysts have caused great concern due to the huge boost of catalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the final reduction step, the use of sodium borohydride (NaBH 4 ) as chemical reductant is a promising method at room temperature to obtain metallic gold nanoparticles with very narrow size distribution . Its potential has also been proved for other metals, such as Pd, Pt, and Sn . However, the combination of these two steps is still relatively unexplored in the literature, especially for low metal loadings.…”
Section: Introductionmentioning
confidence: 99%